2005
DOI: 10.1063/1.1896361
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanism and kinetics of the NCN+NO reaction: Comparison of theory and experiment

Abstract: The rate constants for the NCN + NO reaction have been measured by laser photolysis/laser-induced fluorescence technique in the temperature range of 254-353 K in the presence of He (40-600 Torr) and N2 (30-528 Torr) buffer gases. The NCN radical was produced from the photodissociation of NCN3 at 193 nm and monitored with a dye laser at 329.01 nm. The reaction was found to be strongly positive-pressure dependent with negative-temperature dependence, as was reported previously. The experimental data could be rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(68 citation statements)
references
References 33 publications
8
59
1
Order By: Relevance
“…These authors observed delayed rise times of the 3 NCN fluorescence signals on the order of 15 μs that were attributed to the mechanism of NCN formation via photolysis of CH 2 N 2 /C 2 N 2 mixtures. Huang et al [31] and Yang et al [32], using the same detection technique but photolysis of NCN 3 at 193 nm as NCN source, did not report any delayed formation of NCN.…”
Section: Ncnmentioning
confidence: 99%
“…These authors observed delayed rise times of the 3 NCN fluorescence signals on the order of 15 μs that were attributed to the mechanism of NCN formation via photolysis of CH 2 N 2 /C 2 N 2 mixtures. Huang et al [31] and Yang et al [32], using the same detection technique but photolysis of NCN 3 at 193 nm as NCN source, did not report any delayed formation of NCN.…”
Section: Ncnmentioning
confidence: 99%
“…As mentioned in the introduction part, there are some studies concerning the IR spectra of cyanogen azide molecule [12][13][14][15][16][17][18], whereas there is no corresponding study about the charged forms of cyanogen azide molecule in the literature, to the best of our knowledge. Since (to the best of our knowledge), no experimental data are available for the charged forms of cyanogen azide in the literature; we could not compare the calculated IR data with any experimental one.…”
Section: Resultsmentioning
confidence: 95%
“…According to the experimental and calculated bond length values, the shortest bond length Table 1 Calculated and experimental geometrical parameters of neutral cyanogen azide molecule Ref. [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations